IFPRI Strategy 2016-2018: Capacity strengthening - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
This strategy document identifies the International Food Policy Research Institute’s (IFPRI’s) priority areas of capacity development for food and agricultural policy research, policy formulation, and implementation. It also identifies where IFPRI could increase its investment based on its comparative advantage and how it can continue to deliver high-quality capacity development programs.